AGRO-FOOD MARKET IN THE CONDITIONS OF GLOBALIZATION: WORLD EXPERIENCE OF REGULATION AND INFRASTRUCTURE-INSTITUTIONAL DEVELOPMENT (INNOVATIVE ECONOMY, 2019)
Horlachuk M.A. AGRO-FOOD MARKET IN THE CONDITIONS OF GLOBALIZATION: WORLD EXPERIENCE OF REGULATION AND INFRASTRUCTURE-INSTITUTIONAL DEVELOPMENTPurpose. The aim of the article is assessment of trends and challenges of the current development of the agro-food market in the context of globalization, substantiation of its own developments and proposals regarding the solution of actual scientific and practical problems of the agro-food market of Ukraine, taking into account the world experience of its regulation and infrastructure and institutional support.Methodology of research. Theoretical and methodological basis of the research are scientific provisions, which are reflected in the works of Ukrainian and foreign scientists on the relevant issues of scientific exploration. The following tasks are used in solving the tasks: abstract and logical method – in order to systematize the main stages of development of the European agro-food market in the conditions of globalization processes, to diagnose the current state of the domestic market of agro-food products and to formulate conclusions; analysis and synthesis – to identify relationships in the process of typing market organization in the regulation of individual markets for agro-food; monographic and comparative methods – in determining the comparative differences of the institutional development of global agro-food markets; graphic – when reflecting changes in the structure of the agricultural budget of the European Union.Findings. The basic stages of development and regulation of the European agro-food market in the conditions of globalization are identified and substantiated, infrastructure-institutional changes of its evolution are covered, starting with the price support of certain food markets and ending with the introduction of the system of direct payments to agricultural producers. A global assessment of the trends in the development of agricultural production is carried out and the agro-food market from the standpoint of food security, the problem of overcoming hunger in the world, the uneven distribution of income.Strategic guidelines for the future development of the EU and Ukraine's agri-food market have been determined on the basis of adherence to the principles of production of quality and environmentally friendly production of products, sustainable and balanced development of all elements of the social and economic system of the agro-food market. Threats of raw material variant of development of the domestic agro-food market are revealed, the factors of its effective development within the framework of socially oriented market economy are substantiated.Originality. The main stages of the infrastructure and institutional development of the European agro-food market have been systematized and regulated in the context of globalization. Diagnostics of the trends of the current state of the domestic market of agro-food products has been carried out on the basis of relevant world experience, which, in addition to existing scientific developments, will allow generalizing approaches in the sphere of formation and implementation of measures for the effective development of the agro-food market of Ukraine.Practical value. The global trends and challenges of the modern development of the agro-food market in the conditions of globalization are scientifically substantiated. The logic of the evolutionary progress of the studied market is implemented in the global experience of regulation and infrastructure-institutional support for the development of the agro-food market, which will be a prerequisite for the development of effective agrarian policy and its implementation at all levels of management of these market processes.Key words: agro-food market; agricultural market; globalization; common agricultural policy; market organization; infrastructure and institutional development; food security; hunger; market regulation.
Keywords: Key words; agro-food market; agricultural market; globalization; common agricultural policy; market organization; infrastructure and institutional development; food security; hunger; market regulation.